2014
DOI: 10.1590/bjft.2014.017
|View full text |Cite
|
Sign up to set email alerts
|

Films and edible coatings containing antioxidants - a review

Abstract: SummaryThe incorporation of natural antioxidants into fi lms and edible coatings can modify their structure, improving their functionality and applicability in foods, such as in fresh-cut fruits. This paper reviews the more recent literature on the incorporation of antioxidants from several sources into fi lms and edible coatings, for application in fruits and vegetables. The use of synthetic antioxidants in foods has been avoided due to their possible toxic effects. Instead, a wide range of natural antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 55 publications
4
42
0
2
Order By: Relevance
“…Previous studies on edible films enriched with antioxidant compounds reported protective effects on the food product studied (Eça and others ; Riveros and others ). Ponce and others studied different edible films (chitosan, CMC, among others) enriched with oleoresins.…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies on edible films enriched with antioxidant compounds reported protective effects on the food product studied (Eça and others ; Riveros and others ). Ponce and others studied different edible films (chitosan, CMC, among others) enriched with oleoresins.…”
Section: Resultsmentioning
confidence: 82%
“…Therefore the application of such composite films prepared from hydrophilic cross-linking agents for food preservation was limited [41,42]. These results indicated that adding cross-linking agent of vanillin, especially the addition amount of 5%, the structure of chitosan film was enhanced by forming a relatively dense network and the capacity of the structural elements were decreased that did not lead to the structural relative movement during the tensile test.…”
Section: Film Water Vapor Permeability (Wvp)mentioning
confidence: 99%
“…Starch is the most applied material to develop biodegradable packings due to the advantages described above. Nevertheless, it presents technological challenges due to its hydrophilic character resulting in reduced mechanical (little flexibility and brittleness) and permeability properties (high water vapor and oxygen permeability) . Therefore native starch is blended with other polymers, different plasticizers or native starches from different botanical origins to enhance the mechanical and barrier properties mantaining the biodegradability …”
Section: Introductionmentioning
confidence: 99%